Does housework lower wages and why? Evidence for Britain - Mark L. Bryan; Almudena Sevilla-Sanz (University of Essex, Institute for Social and Economic Research (ISER), 2008)
Women working full-time in the UK earn on average about 18% per hour less than men (EOC, 2005). Traditional labour economics has focussed on gender differences in human capital to explain the gender wage gap. Although differences in male and female human capital are recognized to derive from different household responsibilities over the life cycle, there is also a lesser-studied and more direct effect of household activities on wages. In a broad economic sense, household activities require effort, which decreases labour market productivity and thus wages. This paper first documents the relationship between housework and wages in Britain and applies a variety of econometric techniques to pin down the effect of housework on wages. It further explores what dimensions of housework are at the root of the relationship between housework and wages. After controlling for unobserved heterogeneity, we find a negative effect of housework on wages for married female workers, but not for single workers or married male workers. We argue that the factors behind the relationship between housework and wages are the type and timing of housework activities as much as the actual time devoted to housework.
Keywords: 330